Aplikasi Social Networking Destinasi Wisata Di Pasuruan Pada Platform Android - Abdul Rokhim; M. Tarmihim Efendi (Jurnal Teknika, 2020)
Pasuruan has many tours of natural, religious, shopping, culinary and cultural tourism that can be visited by tourists, but many tourists do not know it yet. Tourist locations in Pasuruan that are still unknown to the general public, the authors take advantage of technological sophistication, especially the android smartphone to provide applications for tourist destinations with social networking methods. It is expected to facilitate the search process for tourist locations in Pasuruan or to introduce tourism in Pasuruan. Based on the testing and analysis of results, this program can be proven to be very helpful for tourists to find tourism in Pasuruan. This is also one form of introducing tourism in Pasuruan